THE INFLUENCE OF SELF-REGULATED LEARNING AND DIGITAL LITERACY ON ACADEMIC PROCRASTINATION IN VOCATIONAL STUDENTS - Azzahra, Verina Dhiva; Wahono, Puji; Adha, Maulana Amirul (Faculty of Economics and Business, Universitas Negeri Jakarta, 2025)
This research is primarily focused on analyzing the impact of SRL and digital literacy on academic procrastination among vocational high school students majoring in Office Management and Business Services at SMKN 41 Jakarta. A quantitative approach was used with 106 students as a saturated sample. A survey instrument was employed to obtain the data and analyzed using IBM SPSS, encompassing assessments of instrument validity and reliability, as well as classical assumption checks and hypothesis evaluation via multiple linear regression. The results show that: (1) SRL has a significant negative effect on academic procrastination, (2) digital literacy also has a significant negative effect, and (3) both variables together significantly and negatively affect academic procrastination. This research contributes to educational strategies by highlighting the importance of enhancing self-regulated learning and digital literacy to reduce academic procrastination among vocational high school students.